Comparison Perbandingan Efektivitas Alat Semprot Manual dan Mesin Dalam Pengaplikasian Prinsip Bernouli : Studi Kaus Di Kalangan Petani Cikole: Comparison of the Efficiency of Manual and Machine Sprayers in Agricultural Applications - Feri Apryandi; Aulia Shinta Pratama; Najwa Khairun Nisa; Refy Hidayanti; Reva Nur Azizah (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
This research compares the effectiveness of manual and machine sprayers in spraying applications on agriculturalland. Research results show that machine sprayers, such as electric knapsack sprayers, are superior to manualsprayers in several aspects. The use of a machine sprayer increases work efficiency with more even fluiddistribution, reduces operator fatigue, and allows area coverage of up to 1-2 hectares per hour. The average timeneeded to spray one hectare of land using a machine sprayer is around 30-45 minutes. In addition, the use ofmachine sprayers can optimize the use of chemicals by reducing waste due to uneven spraying by up to 20-30%. Interms of long-term operational costs, even though machine sprayers require a larger initial investment (around 20-40% higher than manual sprayers), the resulting efficiency can reduce overall costs by 15-25%.